URGENSI PEMBELAJARAN TAFSIR AL-QUR’AN DALAM KURIKULUM PENDIDIKAN ISLAM DI MADRASAH ALIYAH - Silvia Rahayu; Aulya Putri; Natasya Amelia Loviana; Sarah Salsabila; Patimah; Sangkot Abdullah Efendi Harahap (STKIP Subang, 2025)
The learning of Qur’anic exegesis (tafsir) in Madrasah Aliyah plays an important role in developing students’ comprehensive and contextual understanding of Islam. However, Qur’anic learning in madrasahs often focuses on memorization and textual comprehension, resulting in Qur’anic values not being fully internalized in students’ attitudes and behavior. This study aims to analyze the urgency of Qur’anic exegesis learning within the Islamic education curriculum at Madrasah Aliyah. The research employs a qualitative approach using a literature study method by examining relevant books, scholarly articles, and related sources. The results indicate that Qur’anic exegesis learning plays a strategic role in fostering critical, moderate, and responsible religious understanding, as well as supporting the formation of students’ character and moral values. Therefore, strengthening and optimally integrating Qur’anic exegesis learning into the Islamic education curriculum of Madrasah Aliyah is essential.